Uncertainty modeling : dedicated to Professor Boris Kovalerchuk on his anniversary - Kreinovich, Vladik; Kovalerchuk, Boris (Springer, 2017)
This book commemorates the 65th birthday of Dr. Boris Kovalerchuk, and reflects many of the research areas covered by his work. It focuses on data processing under uncertainty, especially fuzzy data processing, when uncertainty comes from the imprecision of expert opinions. The book includes 17 authoritative contributions by leading experts.
Keywords: Uncertainty (Information theory); Electronic data processing.; Fuzzy logic.; elektronické knihy; electronic books